Success in Artificial Insemination Quality of Semen and Diagnostics Employed - Lemma, Alemayehu (IntechOpen, 2013)
Artificial insemination has long been the primary tool towards genetic improvement in many domestic animals. Knowledge based decision are increasingly becoming important in this industry. Scientific publications are having greater role in the contribution of research outputs towards an efficient utilization reproductive phenomenon. This book on improving the success of AI through improving the quality of semen and related diagnostics is just one for interested readers.